2018
DOI: 10.1002/jor.24191
|View full text |Cite
|
Sign up to set email alerts
|

Two compartment pharmacokinetic model describes the intra‐articular delivery and retention of rhprg4 following ACL transection in the Yucatan mini pig

Abstract: Treatment of the injured joint with rhPRG4 is based on recent observations that inflammation diminishes expression of native PRG4. Re-establishing lubrication between pressurized and sliding cartilage surfaces during locomotion promotes the nascent expression of PRG4 and thus intra-articular (IA) treatment strategies should be supported by pharmacokinetic evidence establishing the residence time of rhPRG4. A total of 21 Yucatan minipigs weighing $55 kg each received 4 mg of 131 I-rhPRG4 delivered by IA injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 63 publications
(83 reference statements)
1
17
0
Order By: Relevance
“…Full length recombinant human lubricin protein (rhPRG4) was derived from Chinese Hamster Ovary cells (Lubris, LLC). Briefly, the gene encoding the full length 1404 amino acid human PRG4 was inserted into plasmid vectors (Selexis SA), then the protein was subjected to ultrafiltration/diafiltration, a 3-step chromatographic purification process 19 , 74 . rhPRG4 in DMSO (100 µg/mL rhPRG4 in 10 µl DMSO) or DMSO alone was topically applied to the injury site once per week using a Contec™ CONSTIX™ lint-free, non-absorbent applicator (Fisher).…”
Section: Methodsmentioning
confidence: 99%
“…Full length recombinant human lubricin protein (rhPRG4) was derived from Chinese Hamster Ovary cells (Lubris, LLC). Briefly, the gene encoding the full length 1404 amino acid human PRG4 was inserted into plasmid vectors (Selexis SA), then the protein was subjected to ultrafiltration/diafiltration, a 3-step chromatographic purification process 19 , 74 . rhPRG4 in DMSO (100 µg/mL rhPRG4 in 10 µl DMSO) or DMSO alone was topically applied to the injury site once per week using a Contec™ CONSTIX™ lint-free, non-absorbent applicator (Fisher).…”
Section: Methodsmentioning
confidence: 99%
“…These pre-clinical results have gained traction because of the association of anti-histamine usage with decreased OA severity in patient populations 31 . These ndings are particularly interesting since they resemble the effects observed in preclinical models of OA treated with PRG4 8, 22,23 . Therefore, we hypothesized that proteolytic regulation of PRG4 by tryptase β could play a pathogenic role in OA.…”
Section: Introductionmentioning
confidence: 54%
“…The Prg4 −/− mice demonstrated cartilage degeneration which resulted in a defect in skeletal morphology 22 . We and others have demonstrated that PRG4 injections into injured joints of mice 22 , rats 8 , and pigs 23 resulted in a signi cant delay in OA progression. However, PRG4 treatment does not completely stop the progression of OA.…”
Section: Introductionmentioning
confidence: 77%
“…In the present study, equine serum PRG4 decreased (Figure 2) immediately post-race. The immediate decline in serum PRG4 levels may relate to an apparent clearance or transfer to other tissues, possibly to the liver (43). However, apparent decreases in equine serum PRG4 samples (Figure 2) observed at 3 h and 23-h post-race could be associated with elevated serum cytokines after exercise downregulating PRG4 synthesis from the as yet to be determined source of serum PRG4.…”
Section: Discussionmentioning
confidence: 98%